Development of a quantitative method for the detection of enteroviruses in soil. - Hurst, C J (1979)
A method is described for efficiently concentrating enteroviruses from soil. Viruses were eluted from soil by mechanical agitation in high pH glycine buffer containing ethylenediaminetetraacetic acid. The eluted viruses were concentrated on a floc that formed de novo upon adjustment of the soil eluate to 0.06 M aluminum chloride and pH 3.5. Viruses not pelleted with the floc were concentrated by adsorption to and elution from membrane filters. This method yielded an average efficiency of 66% recovery from loamy sand soil for four enteroviruses. Virus recovery from soil was consistently high, with samples ranging in size from 25 to 500 g. The method was used successfully to isolate naturally occurring viruses from soil beneath a wastewater land treatment site. Recovery of enteroviruses by this method form different types of soil was dependent on percentage of clay, surface area, and cation exchange capacity. Recovery was not dependent on soil saturation pH or on percentage of organic matter. This method should prove useful for studying enterovirus migration and survival during the land application of domestic sewage.